Discussing agrochemical themes: an approach through socio-scientific controversies - Eril Medeiros da Fonseca; Leandro Duso; Marilisa Bialvo Hoffmann (Universidade Federal do Norte do Tocantins, 2017)
The theme of "agro-toxicology" in the Rural Education pervades key issues to be problematized, such as the care of rural workers, from the concept of health as something broad, involving access to cultural goods, leisure and communication and still, the collective physical, mental and social well-being. The use of pesticides, in addition to compromising the health of those who work in the field and those who feed on what is produced in the field, brings with it a conception of health that, in addition to suffering and individualizing, affects our biological diversity. The objective of this study is to discuss pesticides and their implications for health, through the approach of Socio-Scientific Controversies (CSC) in Science Teaching and Rural Education.